Malita, Laura & Egetenmeyer, Regina ed (2011) Students' ePortfolio for entering into the labour marketPeter Lang (New York & Bern) isbn 978‐3‐631‐61490‐7 152 pp £23.40 http://www.peterlang.com/index.cfm?event=cmp.ccc.seitenstruktur.detailseiten&seitentyp=produkt&pk=59484&concordeid=261490. (21st December 2012) - Smyth, Robyn
Summary Malita and Egetenmeyer's practical and useful edited volume is for advocates of e‐portfolios for use in the labour market. It is well structured and comprehensive and begins with a short history and essential definitional work. The articles are written in an easy conversational tone that will suit students and many readers from all parts of the education sector. If this book could be relevant to you, I recommend that you borrow a copy for a while. Robyn Smyth